First and Second Graders’ Reading Motivation and Reading Comprehension Were Not Adversely Affected by Distance Learning During COVID-19 - Thomas, Almut E. (Frontiers in Education, 2021)
Many assume that school shutdowns in the wake of the COVID 19 pandemic have significantly impaired students’ achievement and motivations. Of greatest concern given the sudden shift to distance learning are students with inadequate access to digital media and insufficient experience organizing learning processes independently—for example, first and second graders. This study used a natural experiment with 206 elementary students to investigate differences in reading comprehension and reading motivations of students who attended grades one and two during or before the pandemic. Surprisingly, the results revealed no differences in reading comprehension and reading motivation between the groups, contradicting the assumption that the pandemic-driven shift to distance learning would inevitably impair young students’ achievements and motivations.